Latihan Range of Motion (ROM) dan Kompres Hangat Terhadap Peningkatan Kekuatan Otot pada Lansia Stroke: Laporan Kasus - Annisa Putri, Ayu; Pudang Binoriang, Dinasti (Pustaka Galeri Mandiri, 2025)
Stroke is a health problem that is often experienced by the elderly due to decreased heart organ function, with the prevalence of cases increasing with age by 7.4% in the world and in Indonesia 23.6 per-mile. Non-invasive alternative therapy is considered as a complementary therapy that is easy to do, one of which is range of motion (ROM) exercises, which are types of exercises that aim to maintain or improve joint mobility, muscle mass and tone. Warm compresses are a therapy that provides a warm sensation to the skin that can deactivate nerve fibers so that they relax muscles, reduce muscle spasms and pain. According to research, ROM exercises combined with warm compresses have shown effectiveness in increasing muscle strength in stroke patients. The lack of implementation of these interventions due to the limited abilities of the elderly, makes the elderly with stroke experience hemiparesis or continuous weakness of the limbs. This study aims to see the effect of ROM exercises combined with warm compresses on increasing muscle strength in elderly patients with stroke. The research method used is a case report by conducting interventions on the elderly with ischemic stroke who experience hemiparesis in Padukuhan Gunungan, Bambanglipuro, Bantul, Yogyakarta. This research instrument uses blood pressure and muscle strength measurements before and after the intervention. The intervention was given in 8 meetings with a frequency of 1x/week for 60 minutes each session with a therapy aid. The results showed changes in blood pressure before and after the intervention and an increase in the patient's muscle strength. Based on the study, it can be concluded that there is potential for increased muscle strength in the elderly with stroke, but further quasi-experimental studies with larger samples are needed to confirm the existing findings.